Successful treatment of cardiac tamponade with systemic lupus erythematosus using belimumab and hydroxychloroquine - Tomoo Kise; Shigeru Fukuyama; Masatsugu Uehara (Indian Journal of Rheumatology, 2023)
Cardiac tamponade with systemic lupus erythematosus (SLE) is a rare but fatal complication. Although cardiac tamponade is typically managed with pericardiocentesis and medication, there is no definitive treatment for this condition. Herein, we report a case of cardiac tamponade with SLE in a 15-year-old girl. The patient had fever, chest pain, and fatigue for 1 month. She was diagnosed with SLE, and hence, prednisolone treatment was initiated. Her symptoms had alleviated on the 4th day of treatment; however, the following day, she was admitted to our hospital with fever and vomiting. The patient did not show chest pain or dyspnea. She developed hypotension, chest pain, and dyspnea the day after admission. She was diagnosed with cardiac tamponade using echocardiography. After pericardiocentesis, she was administered belimumab and hydroxychloroquine following intravenous methylprednisolone pulses and was maintained with complete remission for 2 years after the discontinuation of prednisolone and mycophenolate mofetil. This case highlights the potential for successful treatment of lupus cardiac tamponade with intravenous methylprednisolone pulses followed by administration of belimumab and hydroxychloroquine.